The Use of Fermented Sago Pulp as Feed for Super-native Chicken for 1-5 Weeks - Roki Rianza; Deni Rusmana; Wiwin Tanwiriah (Fakultas Peternakan, Universitas Padjadjaran, 2019)
The purpose of this study was to determine consumtion, weight gain, and conversion of super-native chicken rations feed with fermented sago pulp. Sago pulp is a potential local resource for alternative poultry feed as well as an energy source, this can be seen from the metabolic content of sago pulp reaching 2340 kcal / kg, crude protein 3.40%, and crude fiber 11.61%. The purpose of this study was to determine consumption, weight gain, and conversion of super native chicken rations fed with fermented sago pulp. The research method is an experiment using a completely randomized design. The treatment ration used was T0 = (0% ASF), T1 = (10% ASF), T2 = (20% ASF) T3 = (30% ASF), Each treatment was repeated five times. Variables observed were ration consumption, weight gain, and ration conversion. The results of the study there were consumption, weight gain T3 (30% ASF), T2 (20% ASF), and T1 (10% ASF) significantly higher than treatment T0 (0% ASF). The lowest avarage ration conversion results are found in treatment T1 which is 2,40. The conclusion that fermented sago pulp (ASF) can be used in super native chicken rations to the level of 30%.